2004
DOI: 10.1002/mats.200300025
|View full text |Cite
|
Sign up to set email alerts
|

Population Balance Model for Miniemulsion Polymerization, 2

Abstract: Summary: The predictions of the model developed in Part 1 of this series are compared with experimental values taken from literature. Initially, the method of solution of the population balance equation and the simulation algorithm are given. Various radical entry mechanisms are discussed in adequate detail. Plausible arguments are given to identify the correct radical entry mechanism. An expression to evaluate the radical exit coefficient is given. Model predictions of a number of variables are discussed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In this work, the potential of miniemulsion polymerization as a means to produce in situ bimodal or very broad particle size distribution is explored. This is based on our previous works 7–10. In the first of these works,7 we had found that the experimentally reported instability by Miller et al11, 12 is due to a broad initial droplet size distribution in which, depending on the nonideality of the costabilizer‐monomer system, the smaller fractions of the distribution may not be stable, leading to a bimodal droplet size distribution.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In this work, the potential of miniemulsion polymerization as a means to produce in situ bimodal or very broad particle size distribution is explored. This is based on our previous works 7–10. In the first of these works,7 we had found that the experimentally reported instability by Miller et al11, 12 is due to a broad initial droplet size distribution in which, depending on the nonideality of the costabilizer‐monomer system, the smaller fractions of the distribution may not be stable, leading to a bimodal droplet size distribution.…”
Section: Introductionmentioning
confidence: 88%
“…A low initial initiator amount or a high emulsifier amount or low reaction temperature or addition of monomer in batch mode rather than semi‐batch mode and faster addition of monomer in semi‐batch mode leads to broader distributions, as found through modeling studies 39, 40. However, compared with the broadness of the distribution obtained using miniemulsion polymerization as characterized in terms of the standard deviation and the polydispersity index, the breadth of the distribution in emulsion polymerization is low 8–11, 39, 40. Thus, the miniemulsion polymerization process offers a greater advantage over conventional emulsion polymerization process in obtaining very broad particle size distributions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this article, the rate of radical entry into the micelles ( R em ; s −1 ) is given as follows: where k mm is the mass‐transfer coefficient of radical entry into the micelles (cm −2 s −1 ), A m is the total surface area of the micelles (cm 2 ), and R tot is the total aqueous‐phase radical concentration (mol/cm 3 ). Here, we use the collisional radical entry model, as we have done in our previous studies 1, 16–19…”
Section: Rate Of Nucleationmentioning
confidence: 99%
“…Here, we use the collisional radical entry model, as we have done in our previous studies. 1,[16][17][18][19] According to the propagational entry model, only radicals derived from water-soluble initiators with a chain length above a critical degree of polymerization (2-3 for styrene) can enter the particles. However, there now exists experimental evidence provided by Tauer et al 20 that persulfate radicals also enter the particles.…”
Section: Rate Of Nucleationmentioning
confidence: 99%